2006
DOI: 10.1016/j.tetlet.2006.09.071
|View full text |Cite
|
Sign up to set email alerts
|

Lewis acid-promoted α-hydroxy β-dicarbonyl to α-ketol ester rearrangement

Abstract: The decarbomethoxylation reaction of a substituted α-hydroxy-α-carbomethoxy pentacyclic substituted ketone, used as an advanced intermediate in the synthesis of the alkaloid aspidophytine, can be elected by heating with MgI 2 in CH 3 CN. The reaction was shown to proceed by a novel α-hydroxy β-dicarbonyl to α-ketol ester rearrangement. It was possible to isolate a carbonate intermediate in 75% yield, thereby providing support for the proposed pathway.The Rh(II)-catalyzed cyclization/cycloaddition cascade of α-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
1
5
0
1
Order By: Relevance
“…Epoxide opening facilitated by abstraction of C18 α-proton leads to an a-alcohol intermediate, which can form the epoxy alkoxide 20 and readily rearrange across the 1,5 diketone system to afford 9 . This last step is analogous to the reported Lewis-acid-promoted conversion of an α-hydroxy β-dicarbonyl compound to a carbonate 21 , 22 . Alternatively, direct addition of Fl-4a-OO-at C21 of 11 may also take place ( Supplementary Fig.…”
supporting
confidence: 65%
“…Epoxide opening facilitated by abstraction of C18 α-proton leads to an a-alcohol intermediate, which can form the epoxy alkoxide 20 and readily rearrange across the 1,5 diketone system to afford 9 . This last step is analogous to the reported Lewis-acid-promoted conversion of an α-hydroxy β-dicarbonyl compound to a carbonate 21 , 22 . Alternatively, direct addition of Fl-4a-OO-at C21 of 11 may also take place ( Supplementary Fig.…”
supporting
confidence: 65%
“…The presence of a Ag n 0 /Ag n + redox couple facilitates a non-classical electron-transfer process, involving chemical reactions interposed between two electron-transfer steps occurring in opposite directions. 34 The reaction was shown to proceed through a novel α-hydroxy β-dicarbonyl to α-ketol ester rearrangement mechanism, which is supported by the isolation of the carbonate (45) intermediate. 33 The decarboxymethylation of substituted α-hydroxy-α-carbomethoxy hexacyclic substituted ketones (43), one of these used as an advanced intermediate in the synthesis of the alkaloid aspidophytine, can be effected by heating with MgI 2 in CH 3 CN in good yields (75-84%) (Scheme 12).…”
Section: Cationic Rearrangementsmentioning
confidence: 92%
“…Metal alkoxides, such as sodium benzylate, in catalytic amounts promote the [2,3]-Wittig rearrangement of silyl enolates (34), to afford the corresponding rearrangement product (35) in good yields at room temperature (Scheme 8). 23 It has been demonstrated that the oxygen anion of initially formed product (36) effectively catalysed the [2,3]-Wittig rearrangement as a Lewis base.…”
Section: Anionic Rearrangementsmentioning
confidence: 99%
“…Bu reaksiyonlarda genellikle dien olarak furan türevi bileşikler kullanılır. [1] Bunun en önemli sebebi furanın tiyofen ve pirole göre daha düşük aromatikliğe sahip olmasıdır. Yine de daha zor reaksiyon veren pirol ve tiyofen türevli bileşikler de diels alder reaksiyonlarında çeşitli ön işlemlerden sonra kullanılabilmektedir [2].…”
Section: Introductionunclassified